On Spirallikeness of Entire Functions - Narjes Alabkary; Saiful R. Mondal (Mathematics)
In this article, we establish conditions under which certain entire functions represented as infinite products of their positive zeros are <semantics>α</semantics>-spirallike of order <semantics>cos(α)/2</semantics>. The discussion includes several examples featuring special functions such as Bessel, Struve, Lommel, and q-Bessel functions.